ANALYSIS OF BUSINESS POSITIONS REQUIRING PROFESSIONAL COMPETENCE CERTIFICATES IN CIVIL AVIATION - Mustafa Emre CİVELEK and Murat ÇEMBERCİ and Fatma Serab ONURSAL and Mustafa Emre CİVELEK and Nagehan UCA and Okşan KİBRİTCİ ARTAR (International Journal of Eurasia Social Sciences, 2017)
Recent data of Civil Aviation in Turkey shows that the sector is getting bigger. With the development of technology, the economic tariff packages created by airline operators with shorter flight times and higher flight frequencies have increased the business volume of the sector. This trend has also increased the demand for human resources in the sector. Human resources trained in the field of civil aviation demanded by the sector have also been taken into consideration by the universities and universities have increased the number of departments/programs and quotas in order to train qualified human resources. However, the lack of curriculum, teaching staff, and foreign language and professional competence certificates in universities creates problems for those trained in civil aviation working in job positions in the sector. This article is the first in Turkey to address these problems within the scope of trainings that provide professional competence certificates, employment figures and enterprises. In the conclusion of the article, a map of professional competence certificates has been developed.